Analysis Of The Influence Of Compensation And Working Environment On Loyalty In American Fast Food Restaurants Employees - Yusuf Ronny Edward; Sugeng Karyadi; Sitti Usmia; Donny Dharmawan; Ngurah Pandji Mertua Agung Durya (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
Determining and analyzing how pay and work environment affect employee loyalty is the goal of this study. In this investigation, a saturation sampling strategy was employed. There were one hundred employees in the sample for this study. This study employed both primary and secondary data collection methods. Armature or questionnaire procedures were utilized to collect primary data for this study. Documentation and literature reviews are the data sources for this study. This study employed a quantitative descriptive analytical approach that involved doing tests for data quality, classical assumptions, and hypotheses. Various findings can be derived from the research conducted, including the following: characteristics related to the work environment have a partial impact on employee loyalty. The relationship between employee loyalty and salary is not entirely linear. Compensation and aspects of the work environment have a simultaneous impact on employee loyalty.